Alfonso de Cartagena on the affair of the Canaries (1436–37): humanist rhetoric and the idea of the nation-state in fifteenth–century Castile - Lawrance, Jeremy (2013)
This paper examines the political and juridical theories expounded in Allegationes super conquesta insularum Canarie contra Portugalenses, a brief prepared in 1436 or 1437 by Alfonso de Cartagena, bishop of Burgos and Castilian legate to the Council of Basel, to present to Pope Eugenius IV the Castilian case for the colonization of the Canary Islands, and to refute Prince Henrique of Portugal’s claim to their conquest. It sets the dispute in the context of medieval theories about Just War and the papal or imperial power to authorize such conquests for the purposes of evangelization or trade, and points to its place within the broader perspective of later disputes on the legality of the Spanish conquest of America; but then shows that Cartagena deliberately sought to remove the question from the ambit of these discussions and to construct instead an argument that the Canaries belonged by right to the ancient Vizigothic province of Tingitania (Roman North Africa), and hence to the Vizigothic monarchy’s heirs, the kings of Castile. In order to dispose of the inconvenient fact that the last Vizigothic king, Roderick, was separated from the reigning Castilian monarch, Juan II, by some seven centuries of Islamic occupation of the Iberian Peninsula, Cartagena developed a theory that the ‘right of rule’ (ius principandi) of a nation resides not in the person of its monarch, but in the transfer to him of that right by its ‘people’. In doing so, the paper argues that Cartagena made an important theoretical step towards the early-modern concept of the ‘state’ as, in Quentin Skinner’s words, ‘the sole source of law and legitimate force within its own territ¬ory and [...] sole appropriate object of its citizens’ allegiances’. The paper seeks further to show how, in developing his argument, Cartagena drew not only upon the resources of Roman law but also upon the civic ideals and rhetoric of early Italian Renaissance humanism.